Preparation and characterization of organic-inorganic hybrid nanomaterials using polyurethane-b-poly[3-(trimethoxysilyl) propyl methacrylate] via RAFT polymerization (eXPRESS Polymer Letters)
A series of novel block-type amphiphilic copolymers have been prepared by copolymerizing methacrylate endcapped oligo-urethane and 3-(trimethoxysilyl) propyl methacrylate (TPM) via the sol-gel process. Copolymers with welldefined end groups and narrow polydispersity were prepared through Reversible Addition Fragmentation Chain Transfer (RAFT) polymerization. As-synthesized copolymer was characterized 1H nuclear magnetic resonance (1H NMR), gel permeation chromatography (GPC), Fourier transform infrared (FTIR). The copolymer precursors self-assembled in form of spherical micelles (in selective solvents) have been hydrolyzed and then condensed via sol-gel process in order to generate polyurethane-silica (PU-SiO2) hybrid materials. The hybrid copolymers thus prepared possess excellent thermal stability and mechanical property. The structures and properties of the copolymer precursors and their hybrid copolymers were characterized by thermogravimetric analysis (TGA), tensile test and atomic force microscopy (AFM).